(untitled) (REMUNOM, 2025)
Burnout syndrome, characterized by emotional exhaustion and low personal achievement, is one of the consequences of overwork. The objective was to analyze the opinions of employees regarding the promotion of mental health in the workplace. The main findings indicate that employees are aware of what Burnout syndrome is (68%); that the level of stress at work is controllable (65%); are physically or emotionally exhausted (65%); have enough time to complete tasks (62%); have support from the team in times of stress (56%); have policies for employee well-being (44%); and have professional support to deal with stress (27%). The study provides a basis for the development of organizational practices aimed at promoting a healthier and more productive work environment.